Analysis of Implementation of Tuberculosis Control and Prevention Program in Purwoyoso Primary Healthcare Center, Semarang City - Nahari Ratu Cempaka Wilis; Hardi Warsono; Mateus Sakundarno Adi (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
ABSTRACTTuberculosis (TB) is one of the ten main causes of the highest mortality rate worldwide. The number of TB cases in Purwoyoso Primary Healthcare Center increased by 61 cases or up to 93 cases in 2019. The success rate of treatment performed in the primary healthcare center reached 72%, still not achieving the national target rate. This study analyzed the implementation of TB prevention and control program in Purwoyoso Primary Healthcare Center for tracking patients with TB and achieving the success rate analyzed from inputs, processes, and outputs according to the national target rate. This study used a qualitative method and a case-study approach through observation and in-depth interviews. There were 7 informants selected using purposive sampling. This study performed data collection, reduction, and verification. The results show different inputs, such as health worker layoffs, and double work load in the fieldwork, abrupt training, and absence of an evaluation, budgeting that was not focused on case tracking and report, resulted in suboptimal processes, such as suboptimal health promotion efforts, case tracking and report, as well as control of risk factors. Hence, the number of cases being reported and the success rate of treatment as the outputs would not be optimal.Keywords: Program analysis, Tuberculosis, Primary Healthcare Center